2012
DOI: 10.1128/mcb.00429-12
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 3 Regulates Immune and Metabolic Homeostasis

Abstract: A nimal growth and development rely on coordinated functions of body organs to balance energy consumption and storage under optimal or challenging conditions, such as food scarcity or pathogen attack. When adverse conditions are temporary, animals survive by lengthening development and postponing maturity, reducing their body size (16,65). In contrast, prolonged starvation or chronic inflammation may exhaust energy reserves, causing death (32, 69). The key nutrient-sensing, metabolic, and immune-signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 77 publications
6
76
0
1
Order By: Relevance
“…Similarly, the transcription factor ATF3 inhibits antimicrobial peptide expression and metabolic storage in larvae; it is difficult to directly compare the function of Atf3 with that of Mef2 because of the many differences in experimental approach, but the function of Atf3 appears broadly opposite to that we ascribe to Mef2. 36 In this regard, it may be relevant that our computational analysis identified an association between CREB/ ATF sites and antimicrobial peptides.…”
Section: Importance Of Cytokine Signalingmentioning
confidence: 96%
“…Similarly, the transcription factor ATF3 inhibits antimicrobial peptide expression and metabolic storage in larvae; it is difficult to directly compare the function of Atf3 with that of Mef2 because of the many differences in experimental approach, but the function of Atf3 appears broadly opposite to that we ascribe to Mef2. 36 In this regard, it may be relevant that our computational analysis identified an association between CREB/ ATF sites and antimicrobial peptides.…”
Section: Importance Of Cytokine Signalingmentioning
confidence: 96%
“…Based on our finding of a potential activation in stress signaling in fly models of SMA, an important question moving forward will be to understand how loss of SMN causes this stress response. By text mining with the stress signatures identified in the SMA models described here, we found that mutations in the Activating transcription factor 3 (Atf3) gene cause a similar dysregulation in immune and metabolic homeostasis (Rynes et al 2012). Among other things, this signaling pathway appears to regulate the cytosolic formation of SMN-containing U-bodies in human cells in response to bacterial pathogens (Tsalikis et al 2015).…”
Section: Rna Signatures Of Diseasementioning
confidence: 99%
“…In silico analysis of the DNM3os promoter showed seven putative cis-binding sites for ATF3; of these, the two sites nearest the transcription start site of DNM3os were required for PlGF-mediated repression. ATF3, as a member of the ATF/CREB family of basic leucine zipper transcription factors, is induced by an array of signals originating from cytokines, physiological changes, and pathological stimuli (20,(39)(40)(41)(42)(43)(44)(45). ATF3 protein can form heterodimers with AP-1 complex, JDP2, and ATF2 (19,41,42,44,46).…”
Section: Discussionmentioning
confidence: 99%